1990
DOI: 10.1161/01.hyp.15.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Race, sex, and family history of hypertension and erythrocyte sodium pump [3H]ouabain binding.

Abstract: We studied the binding properties of [ 3 H]ouabain to erythrocytes from normotensive children (n=83) between the ages of 10 and 18 years (mean resting arterial pressure: 102/57 mm Hg) from normotensive and essential hypertensive parents. Arterial blood pressures of 101/57 and 104/57 mm Hg (subjects with normotensive and hypertensive parents, respectively) were not significantly different between the two groups. Forty-four children had normotensive parents and 39 had hypertensive parents, 51 were white and 32 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…172 Dichtchekenian et al 173 observed higher serum levels of digoxin-like factor in salt-sensitive than salt-resistant patients with hypertension and a significant correlation of those levels with blood pressure; however, a high NaCl diet failed to increase the serum levels of the digoxin-like factor in both groups of patients. Songu-Mize et al 174 showed very low binding affinity for ouabain in erythrocytes from black girls with hypertensive parents.…”
Section: Several Investigatorsmentioning
confidence: 98%
See 1 more Smart Citation
“…172 Dichtchekenian et al 173 observed higher serum levels of digoxin-like factor in salt-sensitive than salt-resistant patients with hypertension and a significant correlation of those levels with blood pressure; however, a high NaCl diet failed to increase the serum levels of the digoxin-like factor in both groups of patients. Songu-Mize et al 174 showed very low binding affinity for ouabain in erythrocytes from black girls with hypertensive parents.…”
Section: Several Investigatorsmentioning
confidence: 98%
“…Some researchers have shown a decrease 174 and others an increase 176 in the V nai of the Na + -K + cotransport system. Some have shown a direct relation between severity of hypertension, decrease in venous compliance, and the Kna, of the Na + -K + cotransport.…”
Section: Several Investigatorsmentioning
confidence: 99%
“…A third consideration is the small number of potential predictors of BP that were examined. Though constrained by finances, personnel, and the need to perform examinations expeditiousry, the measurement of additional variables, e.g., cation transport 45 or socioeconomic status, 46 might have altered the results. Despite these limitations, the data were consistent: black children demonstrated greater pressor reactivity than white children at every examination, and pressor reactivity was more strongly associated in blacks than whites with future BP.…”
Section: -31mentioning
confidence: 99%
“…13,14 Some researchers have found genetic differences between races for particular disease states, such as diabetes 15-17 and hypertension. 18,19 Still other investigators have found that outcome disparities for the uninsured, Medicaid patients, and people of color are at least partially attributable to differences in baseline health characteristics and hospital performance. 20,21 …”
mentioning
confidence: 99%